Differentiating between intrapsychic symptoms and behavioral expressions of borderline personality disorder in relation to childhood emotional maltreatment and emotion dysregulation: an exploratory investigation - Goldbach, Roosmarijn; Neukel, Corinne; Panizza, Angelika; Reinken, Aischa; Krause-Utz, Annegret (European journal of psychotraumatology, 2023)
Severity of borderline personality disorder was related to experiences of childhood maltreatment, mediated by emotion regulation difficulties.The Borderline Symptom List might be useful to differentiate between internalizing symptoms and externalizing symptoms associated with borderline personality disorder.
Gesehen am 23.01.2024